IMPLEMENTASI METODE PEMBELAJARAN KOOPERATIF MODEL THINK-PAIR-SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Abdurrahman Abdurrahman; Khofifuddin Khofifuddin (Nurul Jadid University, 2019)
The chemical learning process in the class is very much supported by students' motivation and interest in following the process of learning activities. If students' interests and motivations are lacking, it will affect student learning outcomes. This also became one of the problems that was manifested in Nurul Jadid High School students. Cooperative learning methods Think-Pair-Share (TPS) model is one of the learning methods that can be applied. This research is a class action research (CAR) through the stages of implementation which includes planning, action, observation, evaluation, and reflection. Classroom action research (CAR) aims to find out how to apply the steps of the cooperative learning model TPS so that it can improve the learning outcomes of class XI MIPA.1 SMA Nurul Jadid after the implementation of the TPS model of cooperative learning. The data of the research shows that the learning method of TPS model can improve student learning outcomes of Class XI MIPA.1 Nurul Jadid Senior High School which consists of three main stages, namely: (1) Think; students are asked to think of answers to questions or problems independently given by the teacher, (2) Pair; the teacher asks students to pair up with their classmates, (3) Share; students are asked to discuss the results or answers of their own thinking and then present the results of their answers to all students in the class.